The little, brown handbook - Fowler, H. Ramsey (Longman, 2007)
The most trusted and authoritative name in handbooks, The Little, Brown Compact Handbook is an easy-to-use reference that will answer any question you may have in grammar, writing, or research. This edition offers the latest information on writing with computers, writing online, analyzing visuals, and researching effectively on the Internet. With clear explanations, a wealth of examples, and quick reference checklists and boxes, The Little, Brown Compact Handbook will makes it easy to find what you need and use the information you find.